Energy transition: modelling the impact on natural gas - Fulwood, M (Oxford Institute for Energy Studies, 2021)
In the debate about the impact of the Energy Transition on the current global energy system it is becoming increasingly clear that there are multiple pathways, technologies and outcomes that can help the world to decarbonize. The two scenarios prepared by the OIES are designed to limit the global temperature rise to well below 2 °C, one scenario which is favourable to natural gas and one which is less favourable. The favourable scenario has gas demand slightly higher than current levels in 2050, but with significant levels of abatement and carbon capture, while the unfavourable scenario has gas demand in 2050 at some 60% of today’s levels, but still with significant levels of abatement. The need to switch from coal to gas in the Asian markets leads to rapid growth in LNG trade in the 2020s, sustained at least through 2040. In the unfavourable case LNG trade declines rapidly in the 2030s, giving rise to potential stranded assets. Both scenarios involve natural gas to a much greater degree than the IEA’s Net Zero pathway but are still consistent with limiting the global temperature rise. We do not suggest that this is “the” answer, but it does offer an alternative view of the future which may be considered more achievable given current infrastructure in place and the important role that gas can clearly play in many regions as an agent of decarbonisation.